Quantification of 1.5 T T1 and T2* Relaxation Times of Fetal Tissues in Uncomplicated Pregnancies. Issue 1 (15th February 2021) - Sethi, Simran; Giza, Stephanie A.; Goldberg, Estee; Empey, Mary‐Ellen E.T.; de Ribaupierre, Sandrine; Eastabrook, Genevieve D.M.; de Vrijer, Barbra; McKenzie, Charles A.
Abstract : Background: Despite its many advantages, experience with fetal magnetic resonance imaging (MRI) is limited, as is knowledge of how fetal tissue relaxation times change with gestational age (GA). Quantification of fetal tissue relaxation times as a function of GA provides insight into tissue changes during fetal development and facilitates comparison of images across time and subjects. This, therefore, can allow the determination of biophysical tissue parameters that may have clinical utility. Purpose: To demonstrate the feasibility of quantifying previously unknown T1 and T2 * relaxation times of fetal tissues in uncomplicated pregnancies as a function of GA at 1.5 T. Study Type: Pilot. Population: Nine women with singleton, uncomplicated pregnancies (28–38 weeks GA). Field Strength/Sequence: All participants underwent two iterative decomposition of water and fat with echo asymmetry and least‐squares estimation (IDEAL‐IQ) acquisitions at different flip angles (6° and 20°) at 1.5 T. Assessment: Segmentations of the lungs, liver, spleen, kidneys, muscle, and adipose tissue (AT) were conducted using water‐only images and proton density fat fraction maps. Driven equilibrium single pulse observation of T1 (DESPOT1 ) was used to quantify the mean water T1 of the lungs, intraabdominal organs, and muscle, and the mean water and lipid T1 of AT. IDEAL T2 * maps were used to quantify the T2 * values of the lungs, intraabdominal organs, and muscle. Statistical Tests: F‐tests were performed to assess the T1 and T2 * changes of each analyzed tissue as a function of GA. Results: No tissue demonstrated a significant change in T1 as a function of GA (lungs [ P = 0.89]; liver [ P = 0.14]; spleen [ P = 0.59]; kidneys [ P = 0.97]; muscle [ P = 0.22]; AT: water [ P = 0.36] and lipid [ P = 0.14]). Only the spleen and muscle T2 * showed a significant decrease as a function of GA (lungs [ P = 0.67); liver [ P = 0.05]; spleen [ P < 0.05]; kidneys [ P = 0.70]; muscle [ P < 0.05]). Data Conclusion: These preliminary data suggest that the T1 of the investigated tissues is relatively stable over 28–38 weeks GA, while the T2 * change in spleen and muscle decreases significantly in that period. Level of Evidence: 3 Technical Efficacy Stage: 2